2006
DOI: 10.1007/s10570-006-9074-z
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of cellulose crystallites in regenerated cellulose fibres under tensile and bending loads

Abstract: The degree of orientation in regenerated cellulose fibres with a diameter of 36lm was determined using position-resolved synchrotron X-ray microbeam diffraction. The fibres were characterized in unstrained condition, under tensile strain, and in bending. A homogeneous distribution of the degree of crystalline orientation (Herman's orientation factor f c = 0.85) across the fibre thickness was found in the unstrained fibre. The degree of orientation of cellulose crystallites increased in a linear manner with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…However, because of their specific cell‐wall architecture, with cellulose fibrils winding around the central fiber cavity in a spiral fashion, natural cellulose fibers are only of limited use as reference for (synthetic) regenerated cellulose fibers. With the exception of Northolt and de Vries12 who report birefringence measurements, only data on the orientation of the crystalline fraction in regenerated cellulose fibers7–9 and cellulose composite films10 are available. In ref 9,.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of their specific cell‐wall architecture, with cellulose fibrils winding around the central fiber cavity in a spiral fashion, natural cellulose fibers are only of limited use as reference for (synthetic) regenerated cellulose fibers. With the exception of Northolt and de Vries12 who report birefringence measurements, only data on the orientation of the crystalline fraction in regenerated cellulose fibers7–9 and cellulose composite films10 are available. In ref 9,.…”
Section: Resultsmentioning
confidence: 99%
“…data on the relationship between fiber stress and crystalline orientation are presented, and it is thus difficult to interpret these results with regard to the relationship between fiber strain and orientation. All other studies cited (refs 7,8,. and10) observed a linear relationship between applied strain and molecular orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation parameter cos 2 u hkl of regenerated cellulose was evaluated from WAXD 2D detector images according to the method reported in the literature (Gindl et al 2006).…”
Section: Recovery Of [Bmim]clmentioning
confidence: 99%
“…A system with compact fiber core, a porous middle zone and a semi-permeable fiber skin. However, Gindl et al (2006) showed that only two different parts within lyocell fiber do exist, skin and core. They observed that studied fibers have uniform skin-core orientation, in contrast, Kong et al (2007) obtained non-uniform skin-core orientation by X-ray diffraction as claimed due to the differences of used beam size (5 × 5 µm vs. 500 nm).…”
Section: Regenerated Cellulosementioning
confidence: 99%